Impact of physical layer impairments on multi-band metro networks - Gomes, Filipa Ferreira (2022)
The traffic increase in optical metro networks will saturate the network capacity in a near future, mainly due to new cloud and 5G services, as well as to an increasing number of network users. The use of other fiber bands, than the usual C-band, is seen as a possible near term solution, for this probable capacity crunch. In this work, a metro network horseshoe topology with nodes capable of switching both C and L-band signals is studied. In particular, we have considered for switching Cband signals, reconfigurable optical add/drop multiplexer and Filterless Drop and Waste (FD&W) node architectures, whereas for switching L-band signals, we have considered only FD&W solutions, both amplified and unamplified. An analytical formalism was developed to assess the impact of the physical layer impairments due to fiber transmission and switching node in a horseshoe network performance. Moreover, the cost and power consumption of the C-band and L-band nodes are analyzed. We concluded that in a network end of life scenario, the L-band nodes cost is 3.5 times higher than the C-band nodes, being 99% of this cost attributed to the transponders. In L-band transmission, a lightpath can cross several spans with 10 or 60 km in the amplified solution. In the unamplified solution, where frequency reuse is allowed, a lightpath consists only on a single 10 km span due to the maximum optical link budget. Considering a -20 dB crosstalk level, a 1.5 dB degradation on the optical power budget is observed.